INOVASI FONOLOGIS DENASALISASI DALAM ISOLEK BONAI ULAKPATIAN - Yanti Riswara (Balai Bahasa Provinsi Riau, 2015)
The paper is aimed at describing a language variation, that is Ulakpatian Bonai isolect in Riau Province. This is a kind of historical linguistic study which is objected to describe a phonological inovation process of denasalisation among nasal phonemes at final positions or at close ultimate sillables in an isolect used by Bonai tribe in Ulakpatian, Rokan Hulu District, Riau Province. Analysis of inavation is based on protomalayic (PM) which is reconstructed by Adelaar.The research applicates top-down method of anaysis which are gaining the results by deductive process. Data of this research are oral speech of Bonai people based on 200 Swadesh words. The data are gathered by conversational and listening methods which applied several techniques. The results of the analysis are presented by formal and informal methods. The research findings reveal that the language of the tribe shows three kinds of denasalisation of phonological innovation at final position which have changed the nasal phonemes of *PM to unnasal ones in isolek Bonai Ulakpatian: (*PM > BU) , i.e. 1) PM *n/-# > []/-#, 2) PM *m/-# > [p]/-#, dan 3) PM * /# > [g]/-#.